Inhibitive behaviour of corrosion of aluminium alloy in NaCl by mangrove tannin - Solhan Yahya,; Afidah Abdul Rahim,; Affaizza Mohd Shah,; Rohana Adnan, (Universiti Kebangsaan Malaysia, 2011)
Anticorrosion potential of mangrove tannins on aluminium alloys AA6061 in NaCl solution has been studied using potentiodynamic polarisation method and scanning electron microscopy (SEM). The study was carried out in different pH of corrosive medium in the absence and presence of various concentrations of tannin. The corrosion inhibition behaviour of the mangrove tannin on AA6061 aluminium alloy corrosion was found to be dependant on the pH of NaCl solution. Our results showed that the inhibition efficiency increased with increasing tannins concentration in chloride solution at pH 6. Treatment of aluminium alloy 6061 with all concentrations of mangrove tannins reduced the current density, thus decreased the corrosion rate. Tannins behaved as mixed inhibitors at pH 6 and reduction in current density predominantly affected in cathodic reaction. Meanwhile, at pH 12, addition of tannins shifted the corrosion potential to more cathodic potentials and a passivating effect was observed in anodic potentials. SEM studies have shown that the addition of tannins in chloride solution at pH 12 reduced the surface degradation and the formation of pits.